Interaction of Chlorella vulgaris: Cell Attachment on Nanocellulose-Based Hydrogel for Sustainable Microalgae Cultivation - Wan Nazihah Liyana Wan Jusoh; Mohd Shaiful Sajab; Nazlina Haiza Mohd Yasin; Peer Mohamed Abdul; Mohd Sobri Takriff (BioResources)
This study explores the potential of nanocellulose-based hydrogel for microalgae cell attachment. The hydrogel, composed of cellulose nanofibrils (CNF) and carboxymethyl cellulose (CMC), indicates feasibility in biomedical and cell culturing applications. It qualifies as an excellent substrate for 3D printing bioink utilizing the liquid deposition modelling technique. The growth of Chlorella vulgaris cells in Bold Basal Media (BBM) solution exhibits similar trends for both the standard culture and the culture media incorporating the CNF/CMC hydrogel. It was observed that the ionic-bond crosslinkers of H2SO4 and CaCl2 in hydrogel formation were more conducive to cell adhesion compared to using covalent-bond crosslinkers of epichlorohydrin. Microalgae cell attachment exhibited the increase of green hue on the hydrogel surfaces, which shows the potential of cell to grow in the presence of CNF/CMC hydrogel.